Sirtuin 6 promotes eosinophil differentiation by activating GATA‐1 transcription factor - Bang, In Hyuk (Aging Cell, 2021)
There is evidence emerging that exposure to cold temperatures enhances alternative activation of macrophages in white adipose tissue (WAT), which promotes adipocyte beiging and adaptive thermogenesis. Although we recently reported that NAD(+)‐dependent deacetylase sirtuin 6 (Sirt6) drives alternatively activated (M2) macrophage polarization, the role of myeloid Sirt6 in adaptive thermogenesis had remained elusive. In this study, we demonstrate that myeloid Sirt6 deficiency impaired both thermogenic responses and M2 macrophage infiltration in subcutaneous WAT (scWAT) during cold exposure. Moreover, the infiltration of Siglec‐F‐positive eosinophils in scWAT and Th2 cytokines levels was reduced in myeloid Sirt6 knockout mice. An ex vivo bone marrow‐derived cell culture experiment indicated that Sirt6 was required for eosinophil differentiation independent of its deacetylase activity. Data from our in vitro experiments show that Sirt6 acted as a transcriptional cofactor of GATA‐1, independent of its catalytic function as a deacetylase or ADP‐ribosyltransferase. Specifically, Sirt6 physically interacted with GATA‐1, and enhanced GATA‐1’s acetylation and transcriptional activity by facilitating its cooperation with p300. Overall, our results suggest that myeloid Sirt6 plays an important role in eosinophil differentiation and fat beiging/adaptive thermogenesis, which is at least in part due to its ability to bind GATA‐1 and stimulate its transcriptional activity.